DESAIN MODIFIKASI TRANSFORMATOR PADA ISOLATED DC-DC BOOST CONVERTER DENGAN TOPOLOGI FULL BRIDGE MENGGUNAKAN APLIKASI FEMM - Vinsensius Anggara Paramayuda; n/a Wijono; Waru Djuriatno (Jurnal Mahasiswa TEUB, 2023)
DC-DC converters are an important component in modern power systems. This converter is used to convert DC voltage from one level to another, which is indispensable in various types of applications ranging from everyday electronic equipment to industrial use. By using an isolated DC-DC full bridge converter, a transformer is needed as a separator between the input and output parts as well as a voltage booster in the boost converter. However, when the primary current flowing is high, the ferrite core of the transformer is easier to saturate, so in this study the authors designed a transformer modification by dividing the transformer into two (split). In addition to reducing the risk of saturation due to current, with the split transformer, it also reduces the vertical dimensions of the transformer (more flat), so that heat dissipation is also getting better. With the two transformers divided, the two transformers are paralleled on the primary side and serialized on the secondary side, this causes the difference in current ratio in the transformer before and after the split. Before the split, the winding ratio was 3:10 while after the split it became 3:5. From simulations and calculations performed on FEMM and Octave, on the secondary AWG 24, the comparison of the simulated primary current with the AWG maximum current in the maximum winding before the split is 0.47%, while in the transformer after the split is 0.2%, on the secondary AWG 22, before the split is 0.9% and after the split is 0.59%, on the secondary AWG 20, before the split is 1.78% and after the split is 0.7%. For the resulting primary copper loss, it shows that the transformer after the split shows a smaller copper loss. For core loss in one transformer before the split is lower with an average of 15 Watts, while core loss in two transformers after the split is greater with an average of 28 Watts. Keywords: Transformer, split, current ratio, copper loss, core loss.